HEMATOPOIETIC EFFECTS OF ETHANOLIC EXTRACT FROM Alternanthera sissoo ON ERYTHROCYTE, HEMOGLOBIN, AND HEMATOCRIT LEVELS IN ANEMIA-INDUCED FEMALE WISTAR RATS - Ratih, Gusti Ayu Made; Aryastuti, Anak Agung Sri Agung; Suryaningsih, Putu Ayu; Dwi Agustini, Desak Gede; Habibah, Nur (Meditory : The Journal of Medical Laboratory, 2025)
Background: Maternal anemia remains a primary global health concern due to its association with adverse pregnancy outcomes and the increased risk of iron deficiency anemia in infants, which may impair neurodevelopment and growth. Although iron supplementation is the standard therapy, its gastrointestinal side effects often limit treatment adherence. Therefore, Brazilian Spinach (Althernanthera sissoo), a plant rich in iron, flavonoids, and antioxidants, offers potential as a natural alternative.Objective: This study aimed to evaluate the hematopoietic effects of the ethanolic extract of Alternanthera sissoo on erythrocyte count, hemoglobin concentration, and hematocrit levels in female Wistar rats (Rattus norvegicus) induced with anemia.Methods: A quasi-experimental study using a completely randomized design (CRD) was conducted with three treatment doses (5, 7.5, and 10 mg/kg body weight). Hematological parameters (Erythrocyte count, Hemoglobin (Hb), and Hematocrit (HCT)) were analyzed using a Hematology Analyzer, followed by statistical testing with one-way ANOVA and Duncan’s Multiple Range Test (DMRT) at a 5% significance level.Results: The 10 mg/kg BW treatment produced the most significant improvement in erythrocyte count, Hb, and HCT levels compared to the other groups.Conclusions: Ethanolic extract of Althernanthera sissoo effectively enhances hematological indices in iron-deficient rats, showing strong potential as a natural nutraceutical supplement for preventing anemia during pregnancy.